2018
DOI: 10.3390/polym10101151
|View full text |Cite
|
Sign up to set email alerts
|

Facile Route for Bio-Phenol Siloxane Synthesis via Heterogeneous Catalytic Method and its Autonomic Antibacterial Property

Abstract: Eugenol, used as bio-phenol, was designed to replace the hydrogen atom of hydrogenterminated siloxane by hydrosilylation reaction under the presence of alumina-supported platinum catalyst (Pt-Al2O3), silica-supported platinum catalyst (Pt-SiO2) and carbon nanotube-supported platinum catalyst (Pt-CNT), respectively. The catalytic activities of these three platinum catalysts were measured by nuclear magnetic resonance hydrogen spectrometer (1H NMR). The properties of bio-phenol siloxane were characterized by Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Eugenol of 98% purity was purchased from Guangdong Tongcai New Material Corporation (Guangzhou, China). Carbon nanotube supported platinum catalyst (Pt-CNT) with 3% Pt was prepared in Zhongkai University of Agriculture and Engineering (Guangzhou, China) [6]. Diphenyl carbonate of 99% purity was obtained from Guangdong Wengjiang Reagent Corporation (Shaoguan, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eugenol of 98% purity was purchased from Guangdong Tongcai New Material Corporation (Guangzhou, China). Carbon nanotube supported platinum catalyst (Pt-CNT) with 3% Pt was prepared in Zhongkai University of Agriculture and Engineering (Guangzhou, China) [6]. Diphenyl carbonate of 99% purity was obtained from Guangdong Wengjiang Reagent Corporation (Shaoguan, China).…”
Section: Methodsmentioning
confidence: 99%
“…Eugenol has been used in compound modification for its antibacterial activity, thermal stability, and chemical reactivity [1,2,3,4,5]. With the reactive phenol hydroxyl, bio-phenol polysiloxane has been synthesized via facile heterogeneous catalytic route between eugenol and hydrogen terminated polysiloxane [6,7,8]. As a new kind of functionalized polysiloxane, bio-phenol polysiloxane, which has chemical reactivity and antibacterial activity, has been used in the polymer modification [9].…”
Section: Introductionmentioning
confidence: 99%
“…Eugenol (4-allyl-2-methoxyphenol) is a bio-phenol that derives from plants; it is one of the main constituents of plant essential oils, such as camphor oil, clove oil, cinnamon leaf oil, and nutmeg oil [12]. Its molecular structure is characterized by phenol hydroxyl, a carbon methoxy group, and an allyl group.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is reported that eugenol has anticancer and antioxidant properties [18,19]. Moreover, research shows that the phenolic hydroxyl group plays a pivotal role in antimicrobial activity, and methoxy on the ortho carbon could also enhance the antibacterial activity [12,20].…”
Section: Introductionmentioning
confidence: 99%
“…With a soft Si-O-Si main chain, polysiloxane exhibits high and low temperature resistance, weather resistance, hydrophobicity and low-viscosity, and is usually used to modify plastic and rubber [4,5]. Eugenol polysiloxane, a new type of polysiloxane with two phenolic hydroxyl terminal groups, was synthesized via reaction between eugenol and hydrogenterminated polysiloxane, as our previous research reported [6]. Eugenol is a common bio-phenol in the chemical synthesis, and eugenol polysiloxane was used in the polymer modification for its chemical reactivity, antibacterial property and benzene ring which could improve the rigidity of polymer [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%